Bayesian Small Area Cluster Analysis of Neural Tube Defects in Newfoundland - Sloka, J. Scott (Can J Public Health, 2006)
BACKGROUND: The incidence of neural tube defects (NTDs) is declining worldwide due to the implementation of folic acid supplementation programs. Such a program was implemented over 1996–97 in Newfoundland and Labrador, Canada. The geographical distribution of birth incidence was studied prior to and after the implementation of the program to identify regions of residual high incidence. Excess residual cases may potentially be due to genetic causes or incomplete supplementation program implementation. METHODS: Maternal place of residence for all provincial live birth and stillbirth notifications, provincial maternal-fetal medicine referrals, provincial rehabilitation referrals, and all provincial hospitals with NTDs or terminations for NTDs was obtained from 1975 to 2002 for near complete case ascertainment. Bayesian small area analysis was separately performed on cases from 1975–1996 and 1997–2002. The two time periods were compared. RESULTS: Birth incidence of NTDs was noted to decline after 1996, from 5.54/1000 live births to 1.08/1000 live births. 592 cases were found from 1975–1996 and 34 cases from 1997–2002. Relative risk of birth incidence was 0.93–1.18 (95% CI) for 1975–1996 and 0.97–1.02 for 1997–2002 after Bayesian smoothing. One region had an excess of residual cases greater than 34%. CONCLUSIONS: The implications of this observation to the management of the public health initiative imply that overall response to the decrease in cases tends to be uniform across the province, with potentially one area of interest where extra efforts may be devoted.